Analisis Manajemen Waktu Dengan Metode CPM Pada Proyek Rekonstruksi Ruas Jalan Soekarno Hatta Kabupaten Lamongan, Jawa Timur - Nira Galuh Paramitha; Fausta Ari Barata (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
The reconstruction of the Soekarno-Hatta road in Lamongan Regency is part of the Lamongan Smooth Road (JAMULA) priority program and needs to be completed quickly to prevent disruption of the distribution of goods and movement. The purpose of this study is to evaluate the optimal duration for project completion and to identify the activities on the critical path using the Critical Path Method (CPM). This descriptive quantitative study uses a case study approach. The survey data included secondary data such as implementation schedules and technical project documents. The former were collected through field surveys and interviews. The analysis was conducted by calculating the earliest start, earliest finish, and latest finish times for each activity. This allows for summarizing the dependencies between activities and identifying the project's critical path. The results indicate that the most suitable period to complete the reconstruction of the Sukarno-Hatta road section in Lamongan Regency is 45 calendar days, with the main activities on the critical path and insufficient time. The Critical Path Method (CPM) has been proven to be effective in project schedule management. CPM can be used as a basis for planning and scheduling decisions in road infrastructure projects.